Review : Efektivitas Vaksin Antirabies pada Manusia dan Cara Pemberantasan Kasus Rabies yang ada di Indonesia - Sekar Ayu Maharani; Indah Laily Hilmi; Salman Salman (Peneliti.net, 2023)
Rabies (mad dog disease) is a severe infection of the central nervous system by the rabies virus (family Rhabdoviridae, genus Lyssavirrus). This disease is caused by the bite of an animal suffering from rabies which is transmitted to humans. Some animals that are classified as animals at risk of rabies include dogs, cats, monkeys, rabbits, goats, cows and horses. According to WHO, all GHPR sufferers must be given VAR. Anti Rabies vaccine is given in primary care health facilities that can act as a rabies center in rabies endemic areas. The Anti Rabies vaccine is an active vaccine that must be considered in the cold chain starting from the provincial to regional levels so that the virus content contained in it can form an optimal antibody response when injected into the body of GHPR sufferers. The results of the literature review were obtained after going through the literature search and selection process, there were 10 journals that were reviewed simultaneously and carefully.